A handling qualities analysis tool for rotorcraft conceptual designs. (31st May 2018) - Lawrence, B.; Theodore, C. R.; Johnson, W.; Berger, T.
ABSTRACT: Over the past decade, NASA, under a succession of rotary-wing programs, has been moving towards coupling multiple discipline analyses to evaluate rotorcraft conceptual designs. Handling qualities is one of the component analyses to be included in such a future Multidisciplinary Analysis and Optimization framework for conceptual design of Vertical Take-Off and Landing (VTOL) aircraft. Similarly, the future vision for the capability of the Concept Design and Assessment Technology Area of the U.S Army Aviation Development Directorate also includes a handling qualities component. SIMPLI-FLYD is a tool jointly developed by NASA and the U.S. Army to perform modelling and analysis for the assessment of the handling qualities of rotorcraft conceptual designs. Illustrative scenarios of a tiltrotor in forward flight and a single-main rotor helicopter at hover are analysed using a combined process of SIMPLI-FLYD integrated with the conceptual design sizing tool NDARC. The effects of variations of input parameters such as horizontal tail and tail rotor geometry were evaluated in the form of margins to fixed- and rotary-wing handling qualities metrics and the computed vehicle empty weight. The handling qualities Design Margins are shown to vary across the flight envelope due to both changing flight dynamics and control characteristics and changing handling qualities specification requirements. The current SIMPLI-FLYD capability, lessons learned from its use and future developments are discussed.